A multifaceted analysis of OTUD5 integrated MAVS in innate immunity of Primary Biliary Cholangitis - Ran Chen; Yan Sun; Wenlin Tai (PLoS ONE, 2026)
Background Primary biliary cholangitis (PBC) is a chronic autoimmune liver disease characterized by cholestasis caused by intrahepatic small bile duct injury. Promoting the molecular mechanism of OTU deubiquitinase 5 (OTUD5) in the treatment of PBC requires further exploration. This study unraveled the molecular underpinnings of PBC through bio-informatics analysis and experimental verification for the development of targeted therapeutic strategies. Methods This study screened immune-related genes and validated their expression patterns in whole blood of patients with PBC using microarray based on GEO datasets. The expression level of OTU deubiquitinase 5 (OTUD5) was validated in peripheral blood samples using RT-qPCR and immunofluorescence. Subsequently, proteomic bioinformatics analyses were conducted utilizing STRING and InBio Discover databases to predict interactions with the mitochondrial antiviral signalling protein (MAVS). Furthermore, immunochemical and immunofluorescence analyses of MAVS expression in liver tissues were conducted with a thorough analysis of immune cell infiltration specific to the disease by utilizing single-cell RNA sequencing (scRNA-seq) technology in peripheral blood mononuclear cells (PBMCs) derived from both patients with PBC and healthy controls. Results Compared with those of healthy controls, the liver tissues of patients with PBC presented increased NK cell activation, monocyte/mast cell numbers, and eosinophil numbers. Compared with those in 10 healthy controls, the expression of OTUD5 and MAVS was increased in 16 tissues of patients with PBC. High expression of OTUD5-MAVS in subpopulation 11 mononuclear macrophages was screened by PBMC scRNA-seq, and mononuclear cells with the subgroup 11 phenotype presented highly differentiated characteristics. The expression of OTUD5 and MAVS was inhibited in RAW264.7 cells when OTUD5 was knocked down (P < 0.05). Conclusion This study focused on the overexpression of OTUD5 and its interaction with MAVS within macrophage subset 11 in patients with primary biliary cholangitis (PBC). The expression of OTUD5 and MAVS is increased in patients with PBC and is a potential target for the diagnosis and treatment of PBC.